2013
DOI: 10.1111/1744-9987.12123
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin Predicts the Risk of Mortality in Type 2 Diabetic Patients on Hemodialysis: Evaluation of a Target Level for Improving Survival

Abstract: Glycated albumin (GA) is considered a more reliable marker than glycated hemoglobin (HbA1c) for monitoring glycemic control, particularly in diabetic hemodialysis patients. We investigated the associations of GA, HbA1c, and random serum glucose levels with survival, and evaluated possible targets for improving survival in diabetic hemodialysis patients. In this prospective, longitudinal, observational study, we enrolled 90 diabetic hemodialysis patients across six dialysis centers in Japan. The median duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…The authors concluded that hyperglycemia may have a small direct influence on survival and that, as previously reported [61,62], mortality in ESRD is mainly driven by advanced atherosclerosis and other cardiovascular risk factors. In fact, as described in more detail in the next section, GA levels were associated with CVD but not with any increase in CVD mortality, as observed in other studies [18,45,[63][64][65][66].…”
Section: Glycated Albumin and Survivalsupporting
confidence: 77%
“…The authors concluded that hyperglycemia may have a small direct influence on survival and that, as previously reported [61,62], mortality in ESRD is mainly driven by advanced atherosclerosis and other cardiovascular risk factors. In fact, as described in more detail in the next section, GA levels were associated with CVD but not with any increase in CVD mortality, as observed in other studies [18,45,[63][64][65][66].…”
Section: Glycated Albumin and Survivalsupporting
confidence: 77%
“…Our data showed that GA levels were a better indicator of the glucose fluctuations. A few recent studies have reported finding that high GA levels were associated with increased mortality in diabetic HD patients [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of glycated albumin might, therefore, be a better indicator of glycaemic control than levels of HbA1c in these patients. Several studies have shown positive associations between levels of glycated albumin and all-cause or cardiovascular mortality in diabetic patients on haemodialysis 130135. Notably, no significant associations between average HbA1c levels and mortality were reported.…”
Section: Glycaemic Control Indices and Targetsmentioning
confidence: 99%